Family Doctor Contract Services and Awareness of Blood Pressure Measurement Among Hypertension Patients: A Cross-Sectional Study in Rural Shandong, China - Yan, Chen; Yuan, Yemin; Zhao, Dan; Li, Jie; Fu, Peipei; Chen, Yan; Li, Jie; Li, Zhixian; Yang, Shijun; Li, Wenjuan; Gui, Zhen; Peng, Xiuqing; et al. (Frontiers in Public Health, 2022)
Some studies found that family doctor contract services had positive impact on the self-measurement behaviors of hypertension patients. However, evidence concerning the association between family doctor contract services and blood pressure measurement awareness among hypertension patients is not clear. This study aims to explore the relationship between family doctor contract services and blood pressure measurement awareness among the hypertension patients in rural Shandong, China. A multi-stage stratified random sampling was adopted in 2018 in Shandong Province to conduct a questionnaire survey among the sample residents, in which 982 hypertension patients were included in the study. Pearson chi-square test, t test and logistic regression model were employed using SPSS 24.0 to explore the association between family doctor contract services and blood pressure measurement awareness. 76.8% of hypertension patients would measure blood pressure regularly. The difference of blood pressure measurement awareness between contracted and non-contracted groups was significant, and the blood pressure measurement awareness of the signing group was still higher than that of the non-signing group when controlling other variables. Blood pressure measurement awareness was associated with family doctor contracted services among aged patients, but this association were not found among middle-aged patients. Factors including gender (P < 0.01), smoking status (P < 0.01), sports habits (P < 0.001), self-reported health (P < 0.001), and distance to the village clinic (P < 0.001) were also found to be associated with the blood pressure measurement awareness of hypertension patients. The government should take efforts to strengthen publicity and education of family doctors and pay more attention to female patients and patients with unhealthy life behaviors to improve the blood pressure measurement awareness.